Health-promoting behaviors among hypertensive adult patients with and without comorbidities in Indonesia: a cross-sectional study† - Wicaksana Anggi Lukman; Artawan I Putu Athia Alit; Destiana Adhe Kurnia (Sciendo, 2022)
The aim of this study was to evaluate health-promoting behaviors among hypertensive patients with and without comorbidities.